Pengaruh Bahasa Daerah Terhadap Menulis Karangan Narasi Kelas Tinggi di SD IT An-Nur Kecamatan Tanjung Morawa - Saragih, Erlina; Harahap, Syarifah Ainun; Ramadhani, Mastari (Medan Resource Center, 2024)
The aim of this research is to determine the influence of regional languages on narrative essay writing at SD IT AN-NUR in Tanjung Morawa District. This type of research is quantitative descriptive research. The author conducted quantitative descriptive research because it involves describing, illustrating, explaining, or explaining data in a way that is easy to understand. This study addressed the use of pre- and post-tests in writing a narrative essay entitled “Environment”. Based on the results of the data analysis presented above, it can be concluded that regional languages have an influence on students when writing narrative essays. The pre-test results for students' narrative essay writing showed an average score of 39.75 with a standard deviation of 15.93366 and a variance of 241.1875, while the average post-test score was 76.5 with a standard deviation of 15.31253 and a Variance was. amounting to 222.73 from a total of 20 students.There is an influence of visual media on regional languages through writing narrative essays at SD IT AN-NUR, Tanjung Morawa District. Based on the results of the data analysis presented above, it can be concluded that regional languages influence narrative essay writing with an F-score of 17.641 and a significance level of 0.000 (p < 0.05) and has a regression coefficient of 0.000. This means that Ha is accepted and Ho is rejected.